Isolation and Characterization of Mouse Specificity Protein 6 Promoter - Ivan Arie Wahyudi; Taigo Horiguchi; Keiko Miyoshi; Taro Muto; Trianna Wahyu Utami; Hiroko Hagita; Takafumi Noma (The Indonesian Journal of Dental Research, 2010)
Specificity protein 6 (SP6) is a member of the SP/Krüppel-like transcription factor family and plays key roles in tooth development. To study its biological roles, it is important to understand the spatiotemporal regulation of Sp6 gene expression. For this purpose, we first identified two separate 5' ends of the Sp6 cDNA by 5' RACE analysis using mouse mandibular RNA. Next, we isolated mouse genomic DNA fragments covering the Sp6 gene including two putative mouse Sp6 promoter regions and generated a series of luciferase reporter constructs. We confirmed the activity of both promoters by a luciferase assay and found strong second promoter activity in dental epithelial cells. Unexpectedly, we also detected potential third promoter activity in the intron 2 of the Sp6 gene. Last, we also found that bone morphogenetic protein and wingless signals could enhance Sp6 promoter activity in dental epithelial cells, suggesting the regulatory roles of two cytokines in Sp6 gene expression during tooth development. Our findings may shed new light on the regulatory mechanisms of Sp6 gene expression and provide a possible linkage between cytokine regulation of Sp6 expression and inductive epithelial and mesenchymal interactions.